EFFECTIVENESS OF LEAFLET, FAN, AND VIDEO TIKTOK ON KNOWLEDGE AND ATTITUDE ABOUT CHRONIC ENERGY DEFICIENCY (CED) AMONG PREGNANT WOMEN IN KADEMANGAN VILLAGE, SUKABUMI DISTRICT - Pebriana, Regi; Kurniasari, Ratih; Andriani, Eka (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Chronic Energy Deficiency (CED) is a long-term nutritional deficiency caused by an imbalance in energy and protein intake, characterized by a body mass index (BMI) <17.00 in adults. In reproductive-age women, including pregnant women, CED is characterized by a body weight <40 kg, a thin appearance, and an upper arm circumference (UAC) <23.4 cm. This research seeks to ascertain the effectiveness of educational materials in the form of leaflets, fans, and TikTok videos on improving knowledge and attitudes of pregnant women toward CED. The method used was a pretest-posttest design that's quasi-experimental approach, involving 30 pregnant selected through purposive sampling. The Paired Sample T-Test was used for data analysis via SPSS version 27. The results showed that all educational media significantly influenced the improvement in attitudes and knowledge of the respondents. The leaflet gave a p-value of 0.01 for knowledge and p = 0.00 for attitude. The fan and TikTok video media gave a p-value of 0.00 for both aspects. Thus, all three media are effective as educational tools to increase pregnant women's awareness and attitudes toward CED. Innovative media such as TikTok videos have also proven to have a positive impact in health education.